First-Time Use of Clinical Pharmacists to Improve Appropriate Antibiotic Prescribing in a Medical ICU in Viet Nam. (October 2020) - Van, Tuan Mai; Pham, Nhu Hiep; Hoang, Thi Lan Huong; Dang, Nhat Tan; Pham, Thi Ngoc Anh; Nguyen, Thanh Huy; Cao, Quoc Tuan; Pham, Vu Thuy Hang; Nguyen, Nga; Vasquez, Amber; Phong, Lan Nguyen Thi; Bui, Hien; et al.
Abstract : Background: Antibiotic overuse has led to increasing rates of antibiotic resistant infections and unnecessary antibiotic costs. Clinical pharmacists can play a key role in optimizing appropriate use of antimicrobials and reducing antimicrobial resistance. However, the role of clinical pharmacists in antimicrobial stewardship is new and not well established in Viet Nam. Objective: We evaluated the use of clinical pharmacists for improved antimicrobial prescribing. Methods: We assembled an antibiotic stewardship program (ASP) team consisting of a clinical pharmacist and a specialist in infection prevention and control in a 60-bed medical intensive care unit (MICU) at Hue Central Hospital in central Viet Nam. During January–September 2018, the ASP team collected baseline antibiotic prescribing days of therapy (DOT) for all antibiotics administered in the MICU. Then, from October 2018 through June 2019, the ASP team reviewed daily positive clinical bacterial cultures and susceptibility results for all patients present in the MICU. They reviewed medical charts, including antimicrobial prescriptions, during week days and only if patient was still in the ICU at the time of ASP rounds. The team recommended changes to antibiotic therapy verbally to physicians and left the decision to change antibiotic therapy to their discretion. The ASP team documented whether their recommendations were accepted or rejected. Statistical significance was determined using the Student t test. Results: The ASP team reviewed 160 medical charts and made 169 ASP recommendations: 122 (72%) to continue current treatment; 24 (14%) to monitor drug levels or obtain diagnostic tests; 10 (6%) to discontinue therapy; 6 (4%) to de-escalate therapy; 5 (3%) to adjust doses; and 2 (1%) to broaden therapy. Only 8 of the recommended changes (5%) were declined by the clinicians. The average monthly DOT for all types of antibiotics declined significantly from 2, 213 to 1, 681 (24% decrease; P = .04). Reductions in DOT for the most common broad-spectrum antibiotics included colistin from 303 to 276 ( P = .75); imipenem-cilastatin 434 to 248 ( P = .06); doripenem 150 to 144 ( P = .85). Piperacillin-tazobactam increased from 122 to 142 ( P = 0.75). Conclusions: We demonstrated that daily review of cultures and antibiotic use decreased overall antibiotic prescribing. Given that few recommendations included discontinuation of therapy, ASP rounds likely raised awareness for clinicians to optimize antibiotic use. Funding: None Disclosures: None